Spatial organization of the structural color system in the quetzal, Pharomachrus mocinno (Aves: Trogonidae) and evolutionary implications - Monge-Nájera, Julián (1994)
The quetzal, Pharomachrus mocinno, is a Neotropical bird whose structural green appears to be cryptic. The electron microscope shows that green barbules are thick segmented ribbons that twist slightly along the main axis and end in a bifid or trifid filament. Pigmented barbules are simpler and may have lateral flaps, Barbules from the browngreen interfase change gradually. Even though the color mechanism is internal, it has a significant influence on feather shape, limited by selection for strength and thermoregulation. These results and computer simulations support the interference air-keratin-melanin model. Irregular organization of the melanin and reduced barbule interlocking are expected when dull coloration is favored, for example, by high predation. The capacity to produce iridescence appears to be an ancient metazoan character lost in amphibians and mammals. Evolutionary convergence of avian structural color is suggested because the specific mechanisms do not parallel phylogeny.